Engineering long-range interactions between ultracold atoms with light. (2nd February 2022) - Xie, T; Orbán, A; Xing, X; Luc-Koenig, E; Vexiau, R; Dulieu, O; Bouloufa-Maafa, N
Abstract: Ultracold temperatures in dilute quantum gases opened the way to an exquisite control of matter at the quantum level. Here we focus on the control of ultracold atomic collisions using a laser to engineer their interactions at large interatomic distances. We show that the entrance channel of two colliding ultracold atoms can be coupled to a repulsive collisional channel by the laser light so that the overall interaction between the two atoms becomes repulsive: this prevents them to come close together and to undergo inelastic processes, thus protecting the atomic gases from unwanted losses. We illustrate such an optical shielding (OS) mechanism with 39 K and 133 Cs atoms colliding at ultracold temperature (<1 μK). The process is described in the framework of the dressed-state picture and we then solve the resulting stationary coupled Schrödinger equations. The role of spontaneous emission and photoinduced inelastic scattering is also investigated as possible limitations of the shielding efficiency. We predict an almost complete suppression of inelastic collisions over a broad range of Rabi frequencies and detunings from the 39 K D2 line of the OS laser, both within the [0, 200 MHz] interval. We found that the polarization of the shielding laser has a minor influence on this efficiency. This proposal could easily be formulated for other bialkali-metal pairs as their long-range interaction are all very similar to each other.